Improcedencia de la declaratoria del abandono en la etapa de ejecución ante la falta de impulso procesal y los bienes gravados con providencias preventivas. - Sangacha Quinatoa Marcia Virginia (2024)
The preventive measures established in the General Organic Code of Processes (2015) are precautionary measures that limit the right of ownership of the defendant over their assets, to ensure compliance with an obligation through the preservation of their assets for a future seizure and auction of them. The execution stage established in the General Organic Code of Processes (2015) aims to guarantee compliance with the obligations that have expired in an execution title. During this phase, the pertinent actions are carried out to enforce compliance with the provisions of the sentence or the corresponding execution title. This stage is crucial because it is the moment in which the effects of judicial decisions materialize, ensuring that the rights recognized by the administration of justice are realized in the material world. Procedural momentum refers to a principle of procedural law, which implies that once a judicial process has begun, it must advance continuously until its conclusion. This progress is the exclusive responsibility of the procedural parties. Abandonment is a procedural figure provided for in the General Organic Code of Processes (2015) that occurs when one or both parties in a judicial process stop carrying out procedural acts that promote the progress of the case, for a period. of a certain time. In the event that abandonment is declared for the first time in the first instance, the plaintiff may file a new claim on the same claims, six months after the declaration of abandonment. 4 It should be noted that in this research project, various types of methodology will be used, such as a mixed qualitative and quantitative method, based on tool and techniques that provide quantifiable data. Also using the scientific method, the objective of which is to solve problems and generate knowledge. Documentary method that allows us to collect both physical and electronic documents, including the laws that are used in this project as a basis for the construction of the theoretical framework. Dogmatic legal method with which doctrinal contributions can be obtained. Deductive method which will allow general legal rules to be extended to particular cases. Inductive method this gives a premise to treat the legal institution of study with particular cases as concrete samples. Keywords: abandonment, execution phase, preventive measures.